Interactions Among Helixes in the Hexa-helix Framework in Warungboto Tourism Village Yogyakarta - Sumarto, Rumsari Hadi; Dwiantara, Lukas; Wijaya, Junior Hendri; Giawa, Analius (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2025)
The Warungboto Tourist Village in Yogyakarta City is strategically located at the city center; however, the number of tourists visiting this village remains insignificant compared to the number of tourists visiting Yogyakarta. Therefore, tourism activities in the Warungboto Tourist Village require further development. This development cannot be carried out independently by the local community but necessitates interaction among various stakeholders. This study aims to describe the interactions among the six helixes present in the Warungboto Tourist Village, namely the Yogyakarta City Government, higher education institutions, industries within the Warungboto Tourist Village, the local community, the environment, and the media (the six-helix model).  This study used descriptive qualitative method. The findings indicate that interactions among these six helixes are essential for the sustainable tourism development of the Warungboto Tourist Village. These results align with the hexa-helix theory, which posits that government, academia, industry, community, environment, and media interaction are vital for sustainable development. Further research can be carried out for the development of tourism in tourist villages through interaction between the government, universities, industrial communities, the media and the environment or other fields.